Celebrity morph game development - Iffri Husairi Ismail (2015)
The algorithm developed in this project will be implemented in a Matlab based game where it presents a morphed photo of 2 celebrities. The user will have to guess and judge the morphed image in a multiple choice or open-ended (user interface). The first step to achieve this is to collect different types of celebrity images. After which, the process of image morphing is done. This project aims to effectively warp one face into another and mix these warped images to achieve a visually pleasing morphing while maintaining the face feature. Other possible methods of morphing have also been implemented along the way. This project hopes to integrate different functions and implement warping, cross dissolve and morphing technique in the morphing game design.